Crystal structure prediction of energetic materials and a twisted arene with Genarris and GAtor. Issue 35 (10th August 2021) - Bier, Imanuel; O'Connor, Dana; Hsieh, Yun-Ting; Wen, Wen; Hiszpanski, Anna M.; Han, T. Yong-Jin; Marom, Noa
Abstract : A molecular crystal structure prediction workflow, based on the random structure generator, Genarris, and the genetic algorithm (GA), GAtor, is successfully applied to two energetic materials and a chiral arene. Abstract : A molecular crystal structure prediction (CSP) workflow, based on the random structure generator, Genarris, and the genetic algorithm (GA), GAtor, is applied to the energetic materials 2, 4, 6-trinitrobenzene-1, 3, 5-triamine (TATB) and 2, 4, 6-trinitrobenzene-1, 3-diamine (DATB), and the chiral arene, 4, 5-dimethylphenanthrene. The experimental structures of all three materials are successfully generated multiple times by both Genarris and GAtor, and ranked as the most stable structures by dispersion-inclusive density functional theory (DFT) methods. For 4, 5-dimethylphenanthrene the evolutionary niching feature of GAtor helps find the experimental structure by penalizing the fitness of over-sampled regions and steering the GA to an under-explored basin. For DATB, a putative structure with a sheet packing motif, which is associated with reduced sensitivity, is found to be very close in energy to the experimental structure and could be a viable polymorph. Principal component analysis of atom-centered symmetry functions is used to compare the crystal structure landscapes of TATB and DATB. Genarris and GAtor exhibit robust performance for diverse targets with varied intermolecular interactions. This work demonstrates the potential of including CSP as a part of the energetic materials development process.